THE EFFECT OF TAX SIMPLIFICATION ON TAXPAYERS’ COMPLIANCE BEHAVIOR: RELIGIOSITY AS MODERATING VARIABLE - Muslichah, Muslichah (University of Merdeka Malang, 2015)
Tax compliance was an important issue for nations around the world as governments searched for revenue tomeet public needs. The importance of tax simplification had long been known as a determinant of compliancebehavior and it became an important issue in taxation research. The primary objective of this study was toinvestigate the effect of tax simplification and religiosity on compliance behavior. This study was conducted inMalang, East Java. Survey questionnaires were sent to 200 taxpayers and only 122 responded. Consistentwith the prior research, this study suggested that the effect of religiosity on compliance behavior was positiveand significant. Religiosity acted as moderating role on the relationship between tax simplification andcompliance behavior. This study was contributed to the compliance literature. The present study also providedpractical significance because the empirical result provided information about compliance behavior to helpgovernment to develop strategies toward increasing voluntary compliance.